Ecomorphological trajectories of reef fish sister species (Pomacentridae) from both sides of the Isthmus of Panama - Aguilar Medrano, Rosalía (2018)
Abstract The vicariance model of biogeography focuses on allopatric speciation through fragmentation from an ancestral biota via a barrier that interrupts gene flow between populations. The evolutionary processes that occur over time in sister species on each side of the vicariance event influence their traits by a compromise between divergence and conservatism. The eastern Pacific and the Caribbean Sea were separated by the Isthmus of Panama ~ 3–6 Mya and allopatric speciation occurred on either side of the isthmus. Differences in ecological conditions on each side of the Isthmus of Panama separating the sister species may have shaped their niches and morphologies over evolutionary time. The objectives of this study were to: (1) analyze the variation in niche, morphology, and size in each pair of sister damselfish species on both sides of the Isthmus of Panama, (2) determine whether these variables show specific patterns on each side of the isthmus, and (3) determine whether these variables are correlated through evolution. The results showed no relationship between morphology and niche, however, size was related to both niche and morphology. Sister damselfish species on either side of the Isthmus of Panama differ in terms of niche, morphology, and size. Nevertheless, they also show similarities, indicating environmental constraints and conservatism. This study describes a model in which adaptation or divergence and conservatism shaped the evolution of sister damselfish species on both sides of the Isthmus of Panama. These mechanisms are fundamental to population biology, and they act in opposite directions. Keywords Damselfish · Reef fish · Vicariance · Isthmus of Panama · Niche · Morphology